INTERAKSI SOSIAL SISWA TUNARUNGU - muya barida (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2022)
The problem of social interaction of deaf students is very diverse. This study aims to describe the social interaction skills of deaf students. The research uses a qualitative approach with a case study method. The research subjects were two deaf students. Data were collected through interview, observation, and documentation studies. The data were analyzed using the Miles and Hubermasn flow, namely data reduction, data presentation, and conclusion drawing. The results showed that each student has different interaction skills starting from aspects of communication, attitudes, group behavior, and social norms. Guidance and counseling teachers should provide social interaction skills training in order to be able to develop their social potential optimally.